Co-occurrence of phonological traits in orthographic replacement of sonorant phonemes - Vaz, Suellen [UNESP]; Chacon, Lourenço [UNESP] (FapUNIFESP (SciELO), 2020)
Purpose: This short presentation aims to indicate phonological features inherent to the sonorant consonant class (nasals and liquids) that might be relatively problematic in the orthographic records of these phonemes. Methods: orthographic replacement in text compositions from children in the first grade of elementary school was analyzed. Data analysis was performed according to the Padrao de Aquisicao de Contrastes (PAC). Results: Results reveal that replacement was distributed between the two classes, and within each subclass, relatively unstable phonological contrasts were detected in the orthographic records of these phonemes. Conclusion: This relative instability of contrasts pointed out phonological issues, as well as issues related to the orthographic complexity of each these segments, thus indicating a non-direct relation between speech and spelling.
Keywords: Children; Language development; Linguistics; Manual writing; Sciences; Speech, language, and hearing